2012
DOI: 10.1260/1747-9541.7.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Coach-Athlete Relationship Maintenance Questionnaire (CARM-Q)

Abstract: This study developed and gained initial evidence for the reliability and validity of a measure of the use of maintenance strategies within the coach-athlete relationship (coach-athlete relationship maintenance questionnaire: CARM-Q). In study one, 50 items were generated based on Rhind and Jowett's COMPASS model, which suggests that conflict management, openness, motivation, positivity, advice, support, and social networks are key strategies for maintaining the quality of coach-athlete relationships. The conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 28 publications
7
36
0
Order By: Relevance
“…Data analysis and results. Item analysis was carried out on the pilot study data using SPSS® (version 24; IBM Corporation, 2016) to identify and delete any items that reduced the reliability of the subscales (Rhind & Jowett, 2012). For an item to be retained, Tabachnick and Fidell (1996) suggested that at least two of the following three criteria should be met: a minimum item-total correlation coefficient of .40, a range of inter-item correlations between .30 and .70, and an increase in the estimate if an item was deleted.…”
Section: Step 4: Pilot Testingmentioning
confidence: 99%
“…Data analysis and results. Item analysis was carried out on the pilot study data using SPSS® (version 24; IBM Corporation, 2016) to identify and delete any items that reduced the reliability of the subscales (Rhind & Jowett, 2012). For an item to be retained, Tabachnick and Fidell (1996) suggested that at least two of the following three criteria should be met: a minimum item-total correlation coefficient of .40, a range of inter-item correlations between .30 and .70, and an increase in the estimate if an item was deleted.…”
Section: Step 4: Pilot Testingmentioning
confidence: 99%
“…The scientific literature shows that the development of measurements related to coach–athlete–parent interpersonal relationships is fragmented. For example, the coach–athlete relationship maintenance questionnaire (CARM-Q) was developed by Rhind and Jowett [28]; the coach-created empowering or disempowering coaching questionnaire (EDMCQ-C) was developed by Appleton, Ntoumanis, Quested, Viladrich and Duda [15]; and Sanders, Morawska, Haslam, Filus, and Fletcher [29] developed a questionnaire that assesses the parent and family adjustment processes (PAFAS). The evaluation of the three elements of the system, namely the coach–athlete–parent interpersonal relationships in youth sport, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the emotions, cognitions and behaviors of the persons within this dyad have been shown to be central in developing meaningful relationships (Jowett and Ntoumanis, 2004). Research has also been conducted around the maintenance of relationships, including the conceptualization of the COMPASS Model and Coach–Athlete Relationship Maintenance Questionnaire (CARM-Q) validation process (Rhind and Jowett, 2010, 2012) which has provided valuable insights of coaches within typical dyads in sport.…”
Section: Introductionmentioning
confidence: 99%
“…Jowett and colleagues have employed a number of methodological approaches for the expansive array of research into the coach–athlete relationship. They have mainly centered around the use of questionnaires for model validation purposes (Jowett and Chaundy, 2004; Jowett and Clark-Carter, 2006; Lafrenière et al, 2008; Olympiou et al, 2008; Jowett, 2009; Adie and Jowett, 2010; Jowett et al, 2012b; Rhind and Jowett, 2012; Yang and Jowett, 2013) and interviews for exploratory investigations (Jowett and Meek, 2000; Jowett, 2003; Jowett and Cockerill, 2003; Rhind and Jowett, 2010; Jowett et al, 2012a; Jowett and Carpenter, 2015). All interviews adopted a semi structured format utilizing open ended questions and prompts where required to elicit deeper insight (Patton, 2002).…”
Section: Introductionmentioning
confidence: 99%